DNA-Based Species Identification of Shark Fins Traded in Thai Markets. - Wanlada Klangnurak; Sirachai Arunrugstichai; Petch Manopawitr; Tassapon Krajangdara (My University, 2022)
Abstract Shark fins are among the most highly prized seafood products in the world with massive consumption in Asia over the past several decades. The demand for shark fins is a major driver of the enormous population declines of elasmobranchs that are generally vulnerable to overexploitation. This study aims to better understand the species composition of shark fin products in Thailand and their conservation statuses by using DNA-based species identification. Various types and sizes of shark fins were collected from 4 locations in Thailand. DNA barcoding method based on a fragment of the cytochrome c oxidase subunit I (COI) gene was applied to species identification. The optional pathway to report any amplified samples to the possible lowest taxonomy level are presented. Fins from at least 13 shark species were found among the samples we collected from Thailand’s markets. The spottail shark (Carcharhinus sorrah ) and the night shark (Carcharhinus signatus ) were the two dominant species presented in this study. The conservation status listed in the IUCN Red List and Thailand Red Data were reported for identifiable species. Size-species specification was also discussed. Species composition reported in shark fin products potentially helps indicate the appropriate conservation action and increases awareness from monitoring the trade in elasmobranch products.
Keywords: Carcharhinus; DNA Barcoding; Overexploitation; Identification and Quantification in Food